Rohila INTEGRATED APPROACHES OF TEACHING WRITING IN ENGLISH LESSONS: INTEGRATED APPROACHES OF TEACHING WRITING IN ENGLISH LESSONS - Boqiyeva, Rohila (Журнал иностранных языков и лингвистики, 2022)
This article discusses the integrated approaches used in teaching writing in English lessons and the ways of planning writing instructions as well as provides methodical recommendations for improving writing skills in students. The article discusses the integration approaches used in teaching writing in English lessons and their advantages, as well as provides guidelines for the development of writing in students.